2015
DOI: 10.1130/g36476.1
|View full text |Cite
|
Sign up to set email alerts
|

The response of the southern Greenland ice sheet to the Holocene thermal maximum

Abstract: To determine the long-term sensitivity of the Greenland ice sheet to a warmer climate, we explored how it responded to the Holocene thermal maximum (8-5 cal. kyr B.P.; calibrated to calendar years before present, i.e., A.D. 1950), when lake records show that local atmospheric temperatures in Greenland were 2-4 °C warmer than the present. Records from five new threshold lakes complemented with existing geological data from south of 70°N show that the ice margin was retracted behind its present-day extent in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 33 publications
6
114
0
Order By: Relevance
“…Based on a synthesis of geologic data like ours, Young and Briner (2015) suggested that the minimum extent of the western GrIS was experienced between~4 and~2 ka. This timing is later, but similar to the minimum GrIS extent (7e4 ka) depicted by Larsen et al (2015). However, both compilations show that in most sectors, the GrIS was steadily retreating, with some pauses during moraine deposition, from~10 to 5 ka.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Based on a synthesis of geologic data like ours, Young and Briner (2015) suggested that the minimum extent of the western GrIS was experienced between~4 and~2 ka. This timing is later, but similar to the minimum GrIS extent (7e4 ka) depicted by Larsen et al (2015). However, both compilations show that in most sectors, the GrIS was steadily retreating, with some pauses during moraine deposition, from~10 to 5 ka.…”
Section: Discussionmentioning
confidence: 84%
“…This was followed by a minimum ice extent between~5.4 and 0.6 ka. Reconstructions of land-terminating ice margins elsewhere in western and southern Greenland also reveal ice margin stability in the early Holocene followed by minimum extent during the latter portion of the Holocene (e.g., Larsen et al, 2011Larsen et al, , 2015. In particular, the ice margin at Paakitsoq (80 km south of our field site) was reconstructed to have been relatively stable between~7.9 and 5.4 ka, followed by its minimum extent between 5.4 and 0.24 ka Håkansson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the presence of a relic of the Laurentide ice sheet may be the origin of modeldata mismatches in the climate of eastern North America (Wohlfahrt et al, 2004), the effect is local and small. Cosmogenic surface exposure ages and threshold lake records (Carlson et al, 2014;Larsen et al, 2015;Sinclair et al, 2016) also suggest that by 6 ka, the Greenland ice sheet was similar in extent to present. The ice-sheet distribution and elevations, land-sea mask, continental topography and oceanic bathymetry should all be prescribed as the same as in piControl in the midHolocene simulation (Table 1).…”
Section: Paleogeography and Ice Sheetsmentioning
confidence: 80%
“…Thus, this record provides well-dated constraints on the Holocene Thermal Maximum (HTM) in this area, which refine previous estimates extrapolated for this region (Kaufman et al, 2004) and is similar to the interval when the Greenland Ice Sheet margin was behind its present limit, broadly constrained to ca. 7-4 ka (Larsen et al, 2015).…”
Section: Holocene Glacier Fluctuations In Southeast Greenlandmentioning
confidence: 99%